1996
DOI: 10.1006/viro.1996.0306
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Major Core Structural Protein (VP7) of Bluetongue Virus, by a Recombinant Capripox Virus, Provides Partial Protection of Sheep against a Virulent Heterotypic Bluetongue Virus Challenge

Abstract: A recombinant capripox virus was constructed containing a cDNA copy of genome segment 7 of bluetongue virus (BTV) serotype 1 from South Africa (BTV 1SA), which expressed high levels of the major BTV core protein VP7 in infected lamb testis (LT) cells. Sheep vaccinated with this recombinant virus developed antibodies to VP7 (detected by ELISA) but no neutralizing antibodies to either the homologous or heterologous BTV serotype, prior to challenge (BTV 1 or BTV 3, respectively). Following challenge with a virule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 0 publications
1
44
1
Order By: Relevance
“…When sheep were vaccinated with a capripox virus encoding for VP7, clinical protection was obtained against heterotypic challenge, although the virus still replicated [99]. The immune effectors involved in the VP7 induced protection were probably CD4 T cells, but their direct functional contribution was not evaluated.…”
Section: 'Helper' T Cell Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…When sheep were vaccinated with a capripox virus encoding for VP7, clinical protection was obtained against heterotypic challenge, although the virus still replicated [99]. The immune effectors involved in the VP7 induced protection were probably CD4 T cells, but their direct functional contribution was not evaluated.…”
Section: 'Helper' T Cell Responsesmentioning
confidence: 99%
“…More recently, a canarypoxbased vector that expressed optimized synthetic genes for VP2 and VP5 (two injections, 22 days apart) elicited high levels of neutralizing antibodies, a differential reactivity to VP7 as compared to sera from infected sheep (DIVA), and strong protection against homologous challenge (BTV-17); such a non replicative canarypox vector is extensively and safely used over the world in other recombinant vaccines [10]. Finally, a replicative capripox encoding for VP2, VP7, NS1 and NS3 (one injection) was partially protective in sheep [78,99]. Thus, recombinant vectors can provide protective immunity with DIVA properties but their efficacy barely reaches that of inactivated vaccines, still requiring several injections for efficient long-term protection.…”
Section: Recombinant Vectorsmentioning
confidence: 99%
“…The common immunogenic properties of these viruses have been used for the preparation of live attenuated vaccines that protect all ruminants against CaPV infection (Kitching et al, 1987). Recombinant CaPVs have also been developed for multivalent vaccination purposes (Berhe et al, 2003;Perrin et al, 2007;Romero et al, 1993;Wade-Evans et al, 1996;Wallace et al, 2006). However, although they are antigenically closely related, restriction enzyme pattern analysis, cross-hybridization studies and, more recently, nucleic acid sequencing have shown that nearly all CaPVs can be grouped according to their host origins Cao et al, 1995;Gershon & Black, 1988;Kitching et al, 1989;Tulman et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Romero et al [94][95][96][97] reported the constructions of recombinant CPV, containing the fusion (F) or haemagglutinin (H) gene of rinderpest virus, and their vaccine efficacy in goats or cattle against rinderpest, peste des petits, or lumpy skin diseases. Wade-Evans et al [121] constructed a recombinant CPV expressing the major core protein VP7 of bluetongue virus (BTV). Vaccination with the recombinant virus provided a partial protection against virulent BTV challenge in sheep.…”
Section: ) Capripox Virusesmentioning
confidence: 99%